New post quantum analogues of Ostrowski-type inequalities using new definitions of left–right ( p , q ) $(p,q)$ -derivatives and definite integrals - Yu-Ming Chu; Muhammad Uzair Awan; Sadia Talib; Muhammad Aslam Noor; Khalida Inayat Noor (Advances in Difference Equations, 2020)
Abstract The main objective of this paper is to introduce a new more elegant notion of left–right ( p , q ) $(p,q)$ -derivative and definite integrals. To show the significance of these concepts, we discuss some of their basic properties. A new generalized ( p , q ) $(p,q)$ -integral identity is also obtained. Utilizing this identity as an auxiliary result we then obtain our main results using the concept of n-polynomial convex functions.